(untitled) (Federal University Gusau Faculty of Education Journal, 2026)
This study investigated Influence of Quest for Materialism on Rate of Cyber-Crime Behaviour among University Undergraduate Students in South-South Geopolitical Zone of Nigeria. The population for this study consisted of 316,280 undergraduates from public universities in South-South geopolitical zone of Nigeria. This study adopted the survey research design using a correlational approach. The sample size for this study was 1,800 undergraduates from twelve public universities in South-South Geopolitical Zone of Nigeria, which was selected using the multi-stage sampling procedure. The instrument for this study was the cyber-crime behaviour and predictors questionnaire. Data collected were analysed using inferential statistics involving linear regression analysis. The finding from this study established that Materialism would not significantly predict undergraduate cyber-crime behaviour. It is recommended that society should re-evaluate the societal norms and values that place too much emphasis on material acquisitions without proper means of income and the get-rich syndrome. Also, it was recommended that parents and guardians should help build strong value systems among their children and wards as they grow. This will help guide them against having excessive love for material things and money and reduce the "get rich" syndrome among our undergraduates.